Business best practices: Lessons for small and medium-sized enterprises - Hashim, Mohd Khairuddin; Ahmad, Sa'ari (UUM Press, 2011)
Findings of past studies suggest that business best practices can help companies to become successful. Nevertheless, a review of the management literature reveals that questions have been raised as to whether the best practices identified in the earlier studies are applicable and relevant to all kinds of companies, including the small and medium-sized enterprises (SMEs).Based on the review of five most documented studies on business best practices, this paper attempts to examine and compare the best practices promoted and prescribed in the management literature.The evidence from the review of the studies indicates that successful companies not only adopted different best business practices but these practices varied from study to study as well as contradicted each other.